Liberal and Deliberative Democracy in the Global South: Models, Functions, Practices - Melisa Ross (Politics and Governance)
Deliberative democracy is a consolidated strand of political theory, its current expansion sustained by ongoing experiments in political practice. Initially, model-based theories framed deliberation as a corrective to shortcomings in liberal democracy. More recent approaches shift the focus away from theoretical models and towards the political problems that deliberation can solve. Yet these approaches, too, suffer from a “Global North bias,” centering theories and cases predominantly from wealthy Western countries. This article turns the gaze towards the Global South to counter this bias. I bring Mark Warren’s problem-based approach into dialogue with evidence from Demo.Reset, a project that documented deliberative practices by 105 practitioners across 22 countries in the Global South, to provide a situated and differential account of the functions of deliberation across global contexts: foster pluralism, develop coalitions, and enable collective action. This category-building effort aims to inform democratic theory with global, plural reflections.